Pengaruh Kepercayaan Merek pada Loyalitas yang Dimediasi oleh Keyakinan pada Atribut Produk Donat - Nurul Aini Widiyastuti; Anton Agus Setyawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of consumer trust and product attributes on loyalty which is mediated by trust in donut consumers. Consumers' assessment of the extent to which their needs and desires are met by the product. Donuts are easy to find in cake shops, malls, restaurants or even the donut shop itself. This phenomenon is characterized by the increasing number of donut brands available, so that consumers are faced with a variety of brand choices such as Dunkin' Donuts, J.CO Donut, Abata Donut, and Donut Boys. In this research, consumer trust, brand attributes (x), brand loyalty (y), and brand trust (z) are used. The sample size consisted of 200 respondents from the public who had purchased one of the Dunkin' Donuts brands, J.Co Donuts, Abata Donuts, or Boys Donuts. This research applies quantitative methods by distributing Google Forms which are distributed via platforms on social media. The findings from this SmartPLS analysis show that brand attributes have a positive impact on increasing brand trust, consumer trust has a positive impact on brand trust, and brand trust has a positive impact on brand loyalty.